Deliberative democracy and corporate constitutionalism: considering corporate constitutional courts - Blanc, Sandrine (Journal of business ethics, 2023)
Committees multiply in firms, whether stakeholder boards or committees, multi-stakeholder initiatives, ethics committees, or oversight boards. These arrangements aim to organise and legitimise the social and political activities of corporations. This article raises the question of the appropriate form of such governance structures. The examples above illustrate three possible ways of legitimising corporate quasi-public social and political activities: deliberation within the company, deliberation outside, and an approach we label corporate constitutionalism. While the first two models have been tested in practice and assessed in theory, the third one is comparatively more recent, both in practice and in theory. This article focuses on the latter model and asks whether corporate constitutionalism offers a suitable addition, or alternative, to deliberation (with or within firms) for legitimising corporate quasi-public social and political activities. It examines the respective merits of the three models and argues that a corporate constitutional court may mitigate some of the limits of deliberative practices alone. It argues the court is needed in weak regulatory environments, whether they are failing or inherently limited.